Effects of dietary n-3 polyunsaturated fatty acids on the nutritional quality of abdomen meat and hepatopancreas in a freshwater crayfish (Astacus leptodactylus) - Harlioglu, Muzaffer Mustafa; Koprucu, Kenan; Harlioglu, Ayse Gul; Yilmaz, Okkes; Yonar, Serpil Mise; Aydin, Sevinc; Duran, Tuba Cakmak (Academic Press Inc Elsevier Science, 2015)
The effects of dietary n-3 polyunsaturated fatty acids (PUFA) on the fatty acid composition, cholesterol and fat-soluble vitamins of abdomen meat and hepatopancreas in a freshwater crayfish (Astacus leptodactylus) were investigated. Results showed that dietary n-3 PUFA ameliorated the chemical quality (fatty acid composition, cholesterol and fat-soluble vitamin content) of abdomen meat and hepatopancreas in both female and male A. leptodactylus. Results also showed that, in general, increasing concentrations of dietary n-3 PUFA lowered the deposition of oleic acid (18:1n-9), linoleic acid (18:2n-6) and total n-6 PUFA, but simultaneously improved the deposition of eicosapentaenoic acid (20:5n-3), docosapentaenoic acid (22:5n-3), docosahexaenoic acid (22:6n-3) and total n-3 PUFA in the abdomen meat and hepatopancreas. For example, total n-3 PUFA in the male abdomen meat of control (D1) was 25.1 +/- 2.1 (% of total fatty acids), but that of diet 4 (D4) was 33.8 +/- 2.1. In addition, it was found that the n-3/n-6 ratio in the abdomen meat and hepatopancreas increased with an increased concentration of dietary n-3 PUFA (0.94 +/- 0.39 for the abdomen meat of male crayfish fed D1 and 1.68 +/- 0.1 for the abdomen meat of male crayfish fed D4; and 0.14 +/- 0.03 for the hepatopancreas of female crayfish fed D1 and 0.45 +/- 0.08 for the hepatopancreas of female crayfish fed D4). However, the level of cholesterol and fat-soluble vitamins in the abdomen meat was unaffected by the dietary n-3 PUFA (except retinol and cholesterol levels for the females). The best fatty acid composition, cholesterol and fat-soluble vitamin values in the abdomen meat were obtained from the crayfish fed experimental D4. For example, 86.2 +/- 6.2 mg/100 g cholesterol was found for the female crayfish fed D4, but that of 74.7 +/- 4.4 mg/100 g for the female crayfish fed D1. In conclusion, dietary n-3 series fatty acid concentrations significantly improved the abdomen meat quality of A. leptodactylus. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Cholesterol; Crayfish; Fat-soluble vitamin; Fatty acid; Abdomen meat composition; Food analysis; Food composition